1992
DOI: 10.1161/01.str.23.8.1167
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of infarct volume and mortality by thrombolysis in a rat embolic stroke model.

Abstract: Background and Purpose: Thrombolytic therapy with recombinant tissue plasminogen activator was tested in a rat embolic stroke model.Methods: The rat carotid territory was embolized with arterial-like microthrombi formed under pressure. Hemispheric cerebral blood flow before and after embolization was measured by the intraarterial Xenon-133 injection method. Fifteen minutes after embolization, 24 rats were treated with 3 mg/kg or 10 mg/kg tissue plasminogen activator, and 27 were treated with saline. Carotid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
0
32
0
2
Order By: Relevance
“…2,9,15,16 Recent data obtained from tPA-deficient mice indicate that tPA may and perfusion-weighted (E through H) MRI of representative rats treated with neuroserpin in combination with tPA (A, B, E, and F) or tPA alone (C, D, G, and H). Reduction in CBF (A and C) and ischemic lesion (E and G) were detected in the ipsilateral MCAsupplied territory in the rat treated with neuroserpin in combination with tPA (A and E) or with tPA (C and G) before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,15,16 Recent data obtained from tPA-deficient mice indicate that tPA may and perfusion-weighted (E through H) MRI of representative rats treated with neuroserpin in combination with tPA (A, B, E, and F) or tPA alone (C, D, G, and H). Reduction in CBF (A and C) and ischemic lesion (E and G) were detected in the ipsilateral MCAsupplied territory in the rat treated with neuroserpin in combination with tPA (A and E) or with tPA (C and G) before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Considerable experimental evidence with the use of thrombolytic agents in animal stroke models has shown that autologous clots can be effectively lysed by thrombolytics and that functional neurological recovery results. 16,17 In the present study we used a novel soluble recombinant form of human CD39 with potent ADPase and ATPase activities and strong inhibitory effects on platelet aggregation. 7 In in vitro studies, solCD39 blocks ADP-induced human platelet aggregation and inhibits collagen and thrombin receptor agonist peptideinduced platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Lyden et al (1989) and Del Zoppo et al (1990) found a similar frequency of hemorrhagic transfor mation of infarctions in rabbit and baboon stroke models regardless of whether the thrombolysis was started 90 or 180 min after induction of ischemia. In our laboratory, we found a significant effect of thrombolysis on clinical recovery, mortality, infarct size, and edema development in three different em bolic stroke rat models (Overgaard et al, 1992a(Overgaard et al, , 1993) when rt-PA was administered 15 min after embolization with almost no hemorrhagic complica tions.…”
mentioning
confidence: 93%